Tipificación de la contravención de abigeato por la falta de proporcionalidad de las penas en el art. 199 del código orgánico integral penal. - Ordoñez Tamay, Jessika Dorila (2018)
The present research work whose theme is "TIPIFICATION OF THE CONTRIGINATION OF ABIGEATO FOR THE LACK OF PROPORTIONALITY OF THE PENAS IN ART. 199 OF THE CODEN INTEGRAL CRIMINAL INTEGRAL" It is so that the objective of this work of investigation is oriented to create a regulation that the regulation of penalty for the crimes and contraventions according to the amount of the robbery or theft of the cattle rustling. The current criminal legislation that governs social activity in Ecuador, establishes in the new Organic Integrated Criminal Code, several new figures that are applied through the accusatory oral system, but with respect to what refers to the violation of cattle, this legislation evidences Failures the same ones that violate principles and constitutional guarantees, as I allow to expose next. It is important to emphasize the importance of the principle of proportionality, the guiding principle of criminal law, which regulates the due penalty to be imposed on each offense in accordance with the gravity of the offense or the degree of harm it causes. It turns out that in the definition of the crime of rustling in Ecuador, the penalty to be imposed for the subtraction of heads of cattle is the same without differentiating in any case the number of heads removed. It is inconsistent that by the abduction of a head of sheep (lamb), which has an average market value of $ 40 dollars, the minimum penalty to be imposed is one year of deprivation of liberty; Such a penalty could result from the abduction of 20 or more heads of cattle. That is to say that from no legal point of view there is due proportionality between the infraction and the sentence, which has repercussions on a serious legal problem which has been fully identified and will be developed in the present research work in order to establish a possible Solution to it. It must be taken into consideration that cattle rustling is a punishable offense and stipulated in many legal codes of most cattle breeding countries and consists of theft or theft of livestock or domestic animals, is typified in various penal codes. The action involves the subtraction of cows, sheep, horses or other animals that are owned by a person. This crime is common in nations that have a developed cattle activity, since animals can have a lot of value. The rustling was a scourge difficult to combat in the nineteenth century. Over the years, various security mechanisms began to be put in place that helped minimize the theft of livestock. Mexico, Argentina and Uruguay are some of the countries that, due to their geographic characteristics and their economic activities, suffer from rustling, but we must not leave aside our country that you are immersed in this forms of activities and therefore of this crime, Therefore, it is believed that it is advisable to reform the Integral Criminal Code in order to create the breach of mercury. Methodologically, the information has been ordered and systematized the cases based on the experiences of the authors and based on the main topics of discussion. The ultimate goal of the work is to improve and improve the laws, policies and implementation of the consumer protection system. The present investigation is structured as follows: The Literary Review, consists of the Conceptual, Doctrinal, Legal and Comparative Framework. Investigative background, definition and analysis of the Ombudsman's Office. Materials and methods of research, consists of scientific method, methods of observation, analysis and synthesis, survey techniques and interviews. Analysis and interpretation of Results, described: Analysis as the interpretation of the results of the survey and interview. Discussion: presentation and analysis of the results of the surveys, interviews and the case study. Conclusions and Recommendations and finally the Proposal for Legal Reform.